Ordinary differential equations: An elementary textbook for students of Mathematics, Engineering, and the Science - Harry Pollard (Dover, 1985)
The book begins with a section that examines the origin of differential equations, defines basic terms and outlines the general solution of a differential equation - the solution that actually contains every solution of such an equation. Subsequent sections deal with such subjects as: integrating factors; dilution and accretion problems; the algebra of complex numbers; the linearization of first order systems; Laplace Transforms; Newton's Interpolation Formalas; and Picard's Method of Successive Approximations